Adsorption of reactive dyes by palm kernel shell activated carbon: application of film surface and film pore diffusion models - Mobarekeh, Mohsen Nourouzi; Chuah, Teong Guan; Choong, Thomas Shean Yaw (World Wide Web Publications, 2009)
The rate of adsorption of two reactive dyes, Reactive Black 5 and Reactive Red E onto palm kernel shell-based activated carbon was studied. The experiment was carried out to investigate three models: film diffusion model, film-surface and film-pore diffusion models. The results showed that the external coefficients of mass transfer decreased with increasing of initial adsorbate concentration. In addition, it was found that the adsorption process was better described by using the two resistance models, i.e. film-surface diffusion.